2015
DOI: 10.1038/srep11445
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane preconditioning provides neuroprotection against stroke by regulating the expression of the TLR4 signalling pathway to alleviate microglial activation

Abstract: Excessive microglial activation often contributes to inflammation-mediated neurotoxicity in the ischemic penumbra during the acute stage of ischemic stroke. Toll-like receptor 4 (TLR4) has been reported to induce microglial activation via the NF-κB pathway. Isoflurane preconditioning (IP) can provide neuroprotection and inhibit microglial activation. In this study, we investigated the roles of the TLR4 signalling pathway in IP to exert neuroprotection following ischemic stroke in vivo and in vitro. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 58 publications
2
62
0
Order By: Relevance
“…The production of pro‐inflammatory mediators leads to the neuronal cell damage of inflammatory surroundings. In recent years, abundant studies provide strong evidence that activated macroglia play a crucial role in the pathogenesis of ischemic stroke . Our data suggested that RMST overexpression in OGD‐stimulated BV2 cells induced neuronal apoptosis, while RMST‐knockdown rescued neuronal apoptosis.…”
Section: Discussionmentioning
confidence: 56%
“…The production of pro‐inflammatory mediators leads to the neuronal cell damage of inflammatory surroundings. In recent years, abundant studies provide strong evidence that activated macroglia play a crucial role in the pathogenesis of ischemic stroke . Our data suggested that RMST overexpression in OGD‐stimulated BV2 cells induced neuronal apoptosis, while RMST‐knockdown rescued neuronal apoptosis.…”
Section: Discussionmentioning
confidence: 56%
“…TLR4 is involved in the immune response to exogenous microbial infection. The first line of defense is the key upstream factor that activates the inflammatory response (Sun et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Although we utilized our best efforts to control for the confounders, monitored systemic physiological parameters, and included proper sham and control groups for appropriate comparisons, we cannot completely exclude any effect of anesthesia or acute effects of surgical trauma on our observations. Isoflurane, for instance, is a neuroprotectant and has profound effects on cerebral blood flow (94)(95)(96)(97)(98). The acute surgical procedures that involved craniotomy may have aggravated inflammatory changes in the tissue, increasing leukocyte adhesion (71).…”
Section: Discussionmentioning
confidence: 99%